A eficiência econômica na produção de vinhos do Rio Grande do Sul (2008-2009) - Hoeckel, Paulo Henrique de Oliveira (2014)
This paper aims to analyze the economic efficiency in wine production in Rio Grande do Sul through Data Envelopment Analysis (DEA). For this, we have used a sample of primary data collected in Rio Grande do Sul, Brazil, based on the crop year 2008/2009. The selection of variables to be analyzed is related to the importance of each inputs in wine production, and these are grouped in raw material, container, labor, fixed costs, identifying costs and other costs considering the main products of this industry are table wine (TW) and fine wine (FW), both appearing as the main items responsible for sales in unit production. For applying the DEA models in this study, the CCR and BCC models with input orientation had been adopted to evaluate the technical and scale efficiency of wineries and also to analyze economic efficiency. One can check that the wineries sample analyzed which produce more than half of the TW and FW wineries are operating at the inefficiency scale due to incorrect production scale. It was also found that the level of economic efficiency of wineries producing TW and FW is low, being only about 13% of them operating under economic efficiency. The group of wineries with allocative inefficiency represented more than 85% of the sampled wineries.